A Literature Appreciation Learning Evaluation at Primary School: A Case Study of Reading Poetry - Suryatin, Eka; Zalmansyah, Achril; Abidin, Zainal (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
This study aims to identify cases of difficulties in learning to read poetry for elementary school students. This research is a case study with data obtained from the case subjects of teachers and students of primary school. Data in the form of learning difficulties behavior was taken by using observation, interview, and documentation techniques. The steps taken include case identification, diagnosis, prognosis, remedial (treatment), evaluation, and follow-up (follow-up). The results showed that the case of difficulty in learning literary appreciation, especially reading poetry, was the class condition and the teacher's factor. The condition of the classroom window that is too low can be overcome by providing a cover in the form of a curtain to block the view of students outside the room, while teachers who do not master the class due to a lack of learning media can be overcome by providing other supporting books besides the main book, magazines, and ‘infocus media.